Usability of a website to promote treatment adherence for adults with HIV - dos Santos Machado , Aiodelle; Ribeiro Primeira , Marcelo; Einloft Kleinubing, Raquel; Eslava Albarracin , Daniel Gonzalo; Ferreira Langendorf, Tassiane; de Mello Padoin , Stela Maris; Cardoso de Paula, Cristiane (Investigación y Educación en Enfermería, 2025)
Objective. To evaluate a website-type care-educational technology aimed at promoting adherence to antiretroviral treatment in adults living with HIV. Methods. This study was based on a Knowledge Translation into Action project developed in two stages: in the first stage, a free-access website was created through collaboration among different research groups; in the second stage, a cross-sectional study was conducted with focus groups and individual interviews with eight participants, using the Assistive Technology Assessment Instrument to evaluate the website’s attributes. Results. The website was established as a digital care-educational technology, providing information supported by scientific evidence on self-efficacy, social support, and quality of life. The proposed issues addressed different situations in the lives of people living with HIV, with the objective of fostering treatment adherence. In the overall assessment conducted by the target audience, the website obtained a mean score of 1.88 (minimum 1.1 and maximum 2.0), being classified as adequate. Suggestions received were incorporated through adjustments in design and content structure. Conclusion. The website can be used by adults living with HIV and by nursing professionals to promote treatment adherence, contributing to self-care and health education.